Phylogenetic relationships and species delimitation among the taxa with propagula in Pseudotaxiphyllum (Plagiotheciaceae, Bryophyta). Issue 2 (22nd October 2014) - LI, Xiao‐Qin; ZUO, Qin; LI, Min; HE, Si; JIA, Yu; WANG, You‐Fang
Abstract: The current circumscription of the eight closely related morphospecies with propagula in Pseudotaxiphyllum Z. Iwats. is extremely unsatisfactory because of the ill‐defined delimitation of the species concepts. In order to determine the systematic positions of these closely related species, a phylogenetic reconstruction was carried out based on molecular analyses of two genomic compartments (chloroplast ndhB, rpl16, trnG, trnL‐F, and nuclear ribosomal internal transcribed spacer (nrITS)) together with a haplotype network analysis and species delimitation assessments by thorough morphological studies. The results of the present study show that P. elegans (Brid.) Z. Iwats. was closely related to P. laetevirens (Dixon & Luisier ex F. Koppe & Düll) Hedenäs and both species together with P. maebarae (Sakurai) Z. Iwats. were resolved as monophyletic clades. Pseudotaxiphyllum arquifolium (Bosch & Sande Lac.) Z. Iwats., P. densum (Cardot) Z. Iwats., P. fauriei (Cardot) Z. Iwats., the Asian populations of P. distichaceum (Mitt.) Z. Iwats. and P. pohliaecarpum (Sull. & Lesq.) Z. Iwats. are morphologically identical. At least three cryptic lineages with undifferentiated morphological or geographical pattern were inferred from this species complex. We propose that the above‐mentioned morphospecies be synonymized under P. distichaceum, and the American ' P. distichaceum ' be replaced by a new name, P. subfalcatum (Austin) X. Q. Li, Q. Zuo & Y. F. Wang, stat. nov. Pseudotaxiphyllum obtusifolium Z. Iwats. & B. C. Tan was treated as P. distichaceum (Mitt.) Z. Iwats. var. obtusifolium (Z. Iwats. & B. C. Tan) X. Q. Li, Q. Zuo & Y. F. Wang, stat. nov.